'Too Young To Drink'. An international communication campaign to raise public awareness of fetal alcohol spectrum disorders. (January 2017) - Bazzo, S.; Black, D.; Mitchell, K.; Marini, F.; Moino, G.; Riscica, P.; Fattori, G.
Highlights: Alcohol consumption during pregnancy is a leading cause of physical and mental disabilities around the world. Increasing awareness of the risks of drinking in pregnancy is considered the first step towards FASD prevention. An international FASD awareness campaign was launched in 2014. It was joined by 53 partner entities from 27 countries. The campaign was developed using the principles of social marketing and was spread internationally through the social media. This is a promising approach to mobilize entities dealing with public health around the world in joined prevention efforts.